P158 Severity of hand vascular involvement as assessed by MRI Digital Artery Volume Index (DAVIX©) predicts worsening of clinical parameters and patient reported outcomes in scleroderma. (20th April 2020) - Danzo, Fiammetta; Gjeloshi, Klodian; Lettieri, Giovanni; Abignano, Giuseppina; Hinton, Mark; Dean, Anne-Maree; Cuomo, Giovanna; Kubassova, Olga; del Galdo, Francesco
Abstract: Background: Neointima proliferation is a key pathologic feature of systemic sclerosis (SSc), causing arterial vessel narrowing and being the recognised culprit pathological lesion in digital ulcers (DUs), pulmonary artery hypertension and renal crisis. Nevertheless, there are no validated imaging techniques to assess the severity of vascular involvement in SSc. We have previously shown digital artery volume index (DAVIX©) assessed with time of right MRI angiography, is a reliable measure of neointima proliferation in the hands. The purpose of our study was to identify the value of DAVIX© in predicting worsening of patient reported outcomes (PROs) and clinical parameters in SSc. Methods: Cross-sectional data were available for 91 patients and complete 12 months follow-up data for 68 patients. Data collected included: modfied Rodnan skin score (mRSS), pulmonary function tests (PFTs), echocardiography, nailfold capillaroscopy, Health Assessment Questionnaire Disability Index (HAQ-DI), and Scleroderma Health Assessment Questionnaire (sHAQ). DAVIX© of the dominant hand was calculated as the % mean of the 4 fingers, employing MeVisLab software. Following analysis of distribution, Spearman or Pearson test were used to determine correlation coefficients, as appropriate (Prism 7). Results: 56/68 were female and median of disease duration was 4 years (IQR 1.91-9). As previously reported DAVIX© correlated with the presence of DUs (p = 0.0093). Considering all patients, DAVIX© correlated with mRSS (r=-0.258, p = 0.017), DLCO% (r = 0.338, p = 0.008) and the pattern of capillaroscopy (r=-0.388, p = 0.001). In patients with DUs, DAVIX© showed a stronger correlation with DLCO% (r = 0.786, p = 0.048). Most importantly, DAVIX© predicted the worsening of HAQ-DI (r=-0.295, p = 0.029), sHAQ (r =-0.333, p = 0.029) and VAS pain (r=-0.269, p = 0.038) independently of the presence of DUs. Conclusion: The quantitative assessment of neointima proliferation in the hand by DAVIX© is a useful imaging biomarker of vascular disease activity. The value of DAVIX© in predicting the worsening of PROs and clinical parameters in overall patients, may offer insights on the role of vascular disease activity in the global progression of SSc. The validation of our data in an independent cohort and the sensitivity to change over time of DAVIX© may aid to the implementation of hand MRI as imaging outcome measure of vascular severity in SSc. Disclosures: F. Danzo None. K. Gjeloshi None. G. Lettieri None. G. Abignano None. M. Hinton None. A. Dean None. G. Cuomo None. O. Kubassova None. F. del Galdo None.